Chitosan modification-enhanced silencing effect of Ad5-shPDGF-D vector in breast cancer cell line MDA-MB-231 - Ekentok Atıcı, Ceyda; Akbuğa, Jülide (Bentham Science Publishers, 2023)
Background: Gene therapeutics are being developed to treat metastatic breast tumors, which are mostly resistant to conventional therapies. Targeting platelet-derived growth factor-D (PDGF-D) is a viable approach because it is known to play roles in angiogenesis and tumor growth. The success of gene therapy is largely dependent on delivery vectors, but both viral and nonviral delivery vectors have their disadvantages. Evolving hybrid vectors are being used to overcome those disadvantages. Objectives: In this study, we aimed to prepare a recombinant adenovirus type-5 (Ad5)/chitosan hybrid vector to deliver shPDGF-D in a breast cancer cell line by the noncovalent coating of the Ad5 surface with chitosan, a natural polymer. Methods: The Ad5/chitosan hybrid vector was prepared by the noncovalent coating of the Ad5 surface with different molecular weights (low and high) and different amounts of chitosan (12.5, 25, and 50 µg), and the effect of silencing PDGF-D was investigated in the MDA-MB-231 cell line. Results: In vitro characterization studies showed that the noncovalent chitosan coating increased the size of the Ad5 particle and changed the surface charge from-16.53 mV to slightly neutral. In vitro cell culture studies also showed that the addition of chitosan with both low (73.61%) and high (65.86%) molecular weight increased the PDGF-D silencing efficiency of the Ad5 vector (42.44%) at 48 hours. While low-molecular-weight chitosan had faster effects, high-molecular-weight chitosan provided a more sustained effect in PDGF-D silencing. Conclusion: The results indicate that noncovalent chitosan modification may improve the therapeutic effects of the Ad5 vector, offering the potential for further in vitro and in vivo experiments.
Keywords: Ad5; Chitosan; PDGF-D; Breast Cancer; Gene Silencing; Hybrid Vector